2004
DOI: 10.1111/j.1462-5822.2004.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica serovar Typhimurium interaction with dendritic cells: impact of the sifA gene

Abstract: SummarySalmonella enterica serovar Typhimurium ( S. Typhimurium) and several mutant derivatives were able to enter efficiently murine bone marrow-derived dendritic cells using mechanisms predominantly independent of the Salmonella pathogenicity island 1 type III secretion system. The levels of intracellular bacteria did not increase significantly over many hours after invasion. Using fluid endocytic tracers and other markers, S. Typhimurium-containing vacuoles (SCVs) were physically distinguishable from early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 72 publications
(91 reference statements)
2
34
0
Order By: Relevance
“…More recently, S. enterica serotype Typhimurium colonization of the murine intestine by biofilm formation was shown to require type 1 fimbriae carrying an adhesive allelic FimH (Boddicker et al, 2002). However, unlike epithelial cell internalization, which requires an active bacterial invasion machinery, the observed uptake of S. enterica serotype Typhimurium by DC was SPI-1-independent, as described recently by others (Kiama et al, 2006;Petrovska et al, 2004;van der Velden et al, 2003). A recent in vitro study with a macrophage cell line showed that the route of entry of SPI-1-induced, non-opsonized and complement-or IgG-opsonized Salmonella influenced their vacuolar surroundings and intracellular gene expression (Drecktrah et al, 2006).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…More recently, S. enterica serotype Typhimurium colonization of the murine intestine by biofilm formation was shown to require type 1 fimbriae carrying an adhesive allelic FimH (Boddicker et al, 2002). However, unlike epithelial cell internalization, which requires an active bacterial invasion machinery, the observed uptake of S. enterica serotype Typhimurium by DC was SPI-1-independent, as described recently by others (Kiama et al, 2006;Petrovska et al, 2004;van der Velden et al, 2003). A recent in vitro study with a macrophage cell line showed that the route of entry of SPI-1-induced, non-opsonized and complement-or IgG-opsonized Salmonella influenced their vacuolar surroundings and intracellular gene expression (Drecktrah et al, 2006).…”
Section: Discussionmentioning
confidence: 60%
“…The novel finding of this study is that the type 1 fimbriae-mediated binding of S. enterica serotype Typhimurium to DCs concomitantly targets the bacteria to the intracellular compartment of these professional migratory cells. The potential effect of fimbrial lectins on the phagocytic process of DCs was not evaluated in other studies (Drecktrah et al, 2006;Eriksson et al, 2003;Petrovska et al, 2004;van der Velden et al, 2003). DCs are known to recognize and take up bacteria and bacterial molecules via different groups of receptors, including C-type lectin and pattern recognition receptors (Geijtenbeek et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, translocated SlrP and SspH2 are not reported to be associated with endosomal membranes, and no effect of these proteins on SIF formation or cellular transport has been reported. A previous study reported that the sifA strain exhibits similar characteristics in macrophages and DC, i.e., the loss of the membrane of the SCV and the escape into the host cell cytoplasm (29). We analyzed whether the reduced inhibition of antigen presentation of the sifA strain is linked to this phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the activity of the SPI1-T3SS in extracellular Salmonella, the SPI2-T3SS is specifically induced by intracellular Salmonella and mediates the translocation of a large number of effector proteins across the phagosomal membrane. Mutant strains deficient in the SPI2-T3SS or specific effector proteins such as SifA are highly attenuated for virulence (1) and have been considered as live attenuated vaccines against typhoid fever (21).…”
mentioning
confidence: 99%